Analysis of volatile aroma-active compounds from a headspace of a novel whiskey glass - Jalo, Ville (My University, 2022)
In the literature part of this thesis the human olfactory sense is explored. Also, individual differences in the sense of smell are studied. Since the study focuses on whiskey the anesthetic effects of ethanol on the olfactory system are explored. The different drinking vessels commonly used with whiskey are introduced and reviewed. A novel whiskey glass was studied for its aroma enhancing effects. The glass was designed to lessen the effect of ethanol anesthesia while nosing a whiskey from the glass. A method for headspace solid-phase microextraction (HS-SPME) was developed which adsorbed volatile compounds from the whiskey glass. The HS-SPME method developed was used to analyze whiskey volatile aroma-active compounds. The compounds were identified and quantitated using gas chromatography-flame-ionization detector (GC-FID). For comparison a whiskey sample is quantitated by direct injection and analyzed using gas chromatography-mass spectrometry (GC-MS). Ethanol evaporation experiments were conducted to verify the working principle of the novel whiskey glass. Gas chromatography-olfactometry (GC-O) was used to recognize that the aroma-active compounds of whiskey extracted from the novel glass can be perceived. The HS-SPME method from the whiskey glass was developed to simulate the natural whiskey nosing conditions to ensure relevant results. Several matters regarding the HS-SPME method were considered. These included duration, timing, closed or open headspace and temperature. With the developed method whiskey odorants known to be in the whiskey sample could be identified. Quantitation of these odorants was more challenging and subsequent analyses showed variation in quantities. GC-O also did not perfectly correlate with quantitation’s indicating that some odor-active compounds were under the detection limit.
Keywords: Whiskey, HS-SPME, Olfactory, GC-MS, GC-O, Aroma, Glass